Red fox takeover of arctic fox breeding den : an observation from Yamal Peninsula, Russia - Rodnikova, Anna; Ims, Rolf Anker; Sokolov, Alexander; Skogstad, Gunhild; Sokolov, Vasily; Shtro, Victor; Fuglei, Eva (Polar Biology, 2011)
Here, we report from the first direct observation of a red fox (Vulpes vulpes) intrusion on an arctic fox (Vulpes lagopus) breeding den from the southern Arctic tundra of Yamal Peninsula, Russia in 2007. At the same time, as a current range retraction of the original inhabitant of the circumpolar tundra zone the arctic fox is going on, the red fox is expanding their range from the south into arctic habitats. Thus, within large parts of the northern tundra areas the two species are sympatric which gives opportunities for direct interactions including interference competition. However, direct first-hand observations of such interactions are rare, especially in the Russian Arctic. In the present study, we observed one red fox taking over an arctic fox breeding den which resulted in den abandonment by the arctic fox. On July 19, eight arctic fox pups were observed on the den before the red fox was observed on the same den July 22. The pups were never seen at the den or elsewhere after the red fox was observed on the den for as long as we stayed in the area (until August 10). Our observation supports the view that direct interference with red fox on breeding dens may contribute to the range retraction of arctic foxes from the southern limits of the Arctic tundra in Russia.